Determination of Benzoate Level in Canned Pickles and Pickled Cucumbers in Food Producing Factories in Markazi Province and those that their Products were Sold in Arak City, Iran - Mostafa Delavar; Rita Ahmadi Araghi; Amir Mohammad Kazemifar; Mahdi Abdollahi; Behnoush Ansari (Iranian Journal of Toxicology, 2012)
Background: Anecdotal information has suggested that sodium benzoate is used with more than permissible doses during production steps of food products especially pickles and pickled cucumbers in food producing factories in Markazi province and other food producing factories . The present study was done to evaluate factual concentration of sodium benzoate in these products. Methods: In this study, 8 samples from canned pickled cucumbers and 10 samples from canned pickles were randomly gathered from food production factories in Markazi province between March and September 2010. Also, 25 samples from canned pickled cucumbers and 15 samples from canned pickles and 7 samples of bulk cargo pickled cucumbers were collected from the other provinces in Arak city. Sodium benzoate level was determined in the samples using UV-VIS spectrophotometry method. The determined values were analyzed by N-par test using SPSS software version 16.0. Results: Sodium benzoate level was near zero in the samples of canned pickles and pickled cucumbers from producing factories. This was 200-400 PPM in 7 samples from bulk cargo pickled cucumbers which was higher than permissible dose. There was not a statistically significant difference between mean benzoate level of canned pickles and pickled cucumbers produced in Markazi providence factories and other food factories. Benzoate level was significantly higher than permissible dose in bulk cargo pickled cucumbers. Conclusion: Food products from production factories do not have higher than permissible level of sodium benzoate; however, this is higher in bulk cargo pickled cucumbers. Hence, stricter control on bulk cargo pickled cucumber products is recommended.